Pendampingan Pembelajaran Al-Qur’an Dan Peningkatan Kualitas Bacaan Al-Qur’an Bagi Anak-Anak TPQ Wihdatul Ulum Masjid Sultan Alauddin Makassar - Almardhiyah, Alaina; Rabbani, Muhammad Aqil; Azizzah, Lailatul; Damayanti, Nurul Resty; Maknun, Hurin In; Ilham, Muthi Adnin; Fadilah, Fadilah (Zad Al-Ummah: Jurnal Pengabdian Masyarakat, 2025)
Qur’anic education is essential and highly needed for all groups of people—children, adults, and the elderly alike. Therefore, improving the quality of Qur'anic recitation is crucial and should be instilled from an early age. Qur’anic education serves as an alternative solution to the various problems found within society. The Qur'anic Education Center (TPQ) is one of the facilities that helps children improve and enhance their Qur'an recitation skills, as well as a means to instill Qur'anic values in them from a young age. As a result, children will be able to read the Qur’an correctly and fluently through the application of various teaching methods used in each TPQ, including the talaqqi and participatory methods, which actively involve children in correcting mistakes in Qur'anic recitation. This community service activity uses a descriptive analysis method, where data is collected through direct observation, and the results show that the talaqqi and participatory methods are highly effective and beneficial for children.